Clinical Utility of Histological and Radiological Evaluations of Tumor Necrosis for Predicting Prognosis in Pancreatic Cancer. Issue 5 (May 2020) - Kudo, Masashi; Kobayashi, Tatsushi; Gotohda, Naoto; Konishi, Masaru; Takahashi, Shinichiro; Kobayashi, Shin; Sugimoto, Motokazu; Okubo, Satoshi; Martin, John; Cabral, Horacio; Ishii, Genichiro; Kojima, Motohiro
Abstract : Objectives: Tumor necrosis is often found in pancreatic ductal adenocarcinoma (PDAC). Objective histological assessment and adequate radiological detection of necrosis could be used as biomarkers for therapeutic decision. However, standardized clinical utility of necrosis remains unknown. Here, we aimed to determine the prognostic potential of histological and radiological evaluations of necrosis. Methods: We investigated histological necrosis in 221 patients, who underwent surgery for PDAC, and classified its size as small (⩽5 mm) or large (>5 mm). We also evaluated poorly enhanced areas on preoperative computed tomography to assess their ability for predicting histological necrosis and postoperative prognosis. Results: Tumor necrosis was found in 115 patients (52%) and was related to tumor area, lymph node metastasis, and lymphovascular invasion. Size of necrosis was significantly associated with tumor area, perimeter of necrosis, circularity of necrosis, number of ruptured cancer glands, and presence of collagen bundle ( P < 0.05 for all). Both presence of necrosis and their size were strongly correlated to postoperative prognosis. Patients with poorly enhanced areas showed worse prognosis ( P < 0.01). Conclusions: Our findings underline the capacity of histological and radiological assessment of tumor necrosis for prognosis prediction in PDAC. Abstract : Supplemental digital content is available in the text.